Hydrogen diffusion and trapping in a steel containing porosities. (1st May 2022) - Yaktiti, A.; Dreano, A.; Carton, J.F.; Christien, F.
Abstract: The effect of porosity on diffusion and trapping of hydrogen in a cast steel was studied using electrochemical permeation (EP) and thermal desorption spectrometry (TDS). A comparison between porous and non-porous samples of the same material was conducted. It was demonstrated that hydrogen was mainly located in cavities. Those cavities behave as reversible traps at room temperature. In addition, hydrogen content increases linearly with increasing volume fraction of porosity. Finally, a method was proposed to estimate the hydrogen fugacity of the solution used for chemical charging, as well as the hydrogen solubility of the material. Highlights: Hydrogen-porosity interaction in a cast steel studied using permeation and TDS. Comparison of H behavior between cast and forged specimens of the same steel. 90% of hydrogen is located in the porosities (voids) at room temperature. Porosities behave as reversible traps at room temperature. Methodology proposed for determination of H fugacity and H material solubility.